2017
DOI: 10.1111/tbed.12600
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Peste des Petits Ruminants in Wild and Domestic Animals in Xinjiang, China, 2013-2016

Abstract: Peste des petits ruminants viruses (PPRVs) re-emerged in China at the end of 2013 and then spread rapidly into 22 provinces through movement of live goats and sheep. In this study, 96 samples of domestic animals and 13 samples of wildlife were analysed for the presence of PPRV infection by ELISA or RT-PCR. Of 96 samples from sheep and goats, 91 were PPRV positive, whereas all of the 13 samples from three wild species, Capra ibex (Capra ibex sibirica), argali (Ovis ammon) and Goitered gazelle (Gazella subguttur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…The authors concluded that the most likely source of the outbreak was animals from livestock markets in Shandong. Previous reports have also analysed the pathogens in the large PPR outbreak in China 2014 (Li et al., , ; Wang et al., ). In the current study, we first detected lineage II PPRV in wild H. inermis , which had never been inoculated with any vaccine and had no history of contact with sick animals.…”
mentioning
confidence: 99%
“…The authors concluded that the most likely source of the outbreak was animals from livestock markets in Shandong. Previous reports have also analysed the pathogens in the large PPR outbreak in China 2014 (Li et al., , ; Wang et al., ). In the current study, we first detected lineage II PPRV in wild H. inermis , which had never been inoculated with any vaccine and had no history of contact with sick animals.…”
mentioning
confidence: 99%
“…The main risk of PPRV to Laos is movement of goats across borders (Balamurugan, Hemadri, et al., ; Dhar et al., ; Kumar et al., ). The outbreak in China during 2013‐14 affected 256 counties including Yunnan, a border province with Laos (Li et al., ; Liu et al., ; Wu et al., ). It is possible that the lack of border security plus illegal movement of animals between countries in the region may spread PPR into Laos and beyond into other ASEAN countries, such as Thailand, Vietnam, Cambodia and Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the lack of border security plus illegal movement of animals between countries in the region may spread PPR into Laos and beyond into other ASEAN countries, such as Thailand, Vietnam, Cambodia and Malaysia. Wildlife crossing borders may also play a role in the spread of PPR into Laos (Li et al., ). Although the National Animal Health Laboratory is capable of providing adequate diagnostic support, veterinary work in Laos relies largely on minimally trained provincial veterinary teams and untrained village veterinary workers and the sector is underfunded, with low capacity to respond in an emergency disease outbreak situation (Bastiaensen et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, white-tail deer challenged with PPRV exhibited clinical signs similar to those in goat (29). Abundant reports of natural infection of PPR disease in gazelles, ibexes, bharals, wild goats (Capra aegagrus), wild sheep (Ovis orientalis) have also been documented (7,14,20,22,23,26,31). Additionally, Barbary sheep (Ammotragus lervia) and Afghan Markhor goat (Capra falconeri) died from PPRV infection, which belongs to lineage IV (21).…”
Section: Ppr Infection In Typical Host or Small Ruminantsmentioning
confidence: 91%